Specialist Medical Education Program (PPDS): A Phenomenological Study at the Faculty of Medicine, Sam Ratulangi University - Iddo Posangi; Joulanda A M Rawis; Henny Nikolin Tambingon; Shelty D.M. Sumual (JR Education, 2025)
Bullying in clinical medical education has increasingly been recognized as a systemic problem that undermines learning quality, resident well-being, and ultimately patient safety. This study examines the dynamics of bullying within the Specialist Medical Education Program (PPDS), particularly Anesthesiology and Intensive Care, at the Faculty of Medicine, Sam Ratulangi University (FK Unsrat), and formulates a comprehensive management model for bullying prevention aimed at reducing residents’ risk of depression. Using a qualitative phenomenological approach, data were collected through Focus Group Discussions (FGD) and in-depth interviews with purposively selected participants, including junior residents, senior residents, and consultants. Findings indicate that bullying is often “mild” in appearance yet persistent, manifesting verbally (humiliating remarks, destructive criticism), socially (information exclusion), symbolically (non-academic errands justified as “tradition”), and administratively (unrealistic deadlines and punitive task allocations). These behaviors are normalized by a seniority culture, rigid academic traditions, and hierarchical structures, which create power imbalances and discourage reporting due to fear of retaliation and negative academic consequences. The study also reveals that existing prevention efforts remain largely normative: formal rules are not explicit about bullying, standard operating procedures (SOPs) are absent, and reporting mechanisms are unclear or distrusted. In response, this study proposes an integrated bullying prevention management model consisting of a dedicated SOP, an independent reporting and protection system, strengthened empathetic communication training, consultant mentoring development, organizational culture reorientation, and continuous monitoring and evaluation. The model positions prevention as an institutional quality assurance agenda in clinical education, linking humane supervision, ethical professionalism, and mental health safeguarding to improved learning outcomes and safer care.